2022
DOI: 10.3390/ijms231810580
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Sleep for the Same Level of Respiratory Disturbance in Children with Prader-Willi Syndrome

Abstract: Debate remains as to how to balance the use of recombinant human growth hormone (rhGH) as an important treatment in Prader-Willi syndrome (PWS) with its potential role in obstructive sleep apnea. This single-center, retrospective study assessed differences in overnight polysomnography results between children with and without PWS and changes in respiratory parameters before and after the initiation of rhGH treatment in those with PWS. Compared with age-, sex-, and body-mass-index-matched controls (n = 87), chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Schaefer et al [32] found a reduction in the severity of respiratory events in children with PWS during GH treatment. Tan et al [33] stated that respiratory parameters did not significantly change with rhGH treatment in children with PWS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Schaefer et al [32] found a reduction in the severity of respiratory events in children with PWS during GH treatment. Tan et al [33] stated that respiratory parameters did not significantly change with rhGH treatment in children with PWS.…”
Section: Resultsmentioning
confidence: 99%
“…They went on to conclude that GH therapy improved body composition and resting energy expenditure (REE), thus potentially enhancing sleep quality and lung function. In contrast, Tan et al [33] found that PWS was not associated with an altered risk of OSA and suggested that the risk and severity of OSA were similar for the patients with PWS and the controls. Interestingly, uninterrupted sleep and sleep efficiency (percentage of time spent sleeping compared to total time in bed) were better in the children with PWS than the controls.…”
Section: Gh Administration and Sleep-disordered Breathingmentioning
confidence: 89%
See 3 more Smart Citations